Radiomics based on MRI in predicting lymphovascular space invasion of cervical cancer: a meta-analysis - Yang, Chongshuang; Wu, Min; Zhang, Jiancheng; Qian, Hongwei; Fu, Xiangyang; Yang, Jing; Luo, Yingbin; Qin, Zhihong (Frontiers in Oncology, 2024)
ObjectiveThe objective of this meta-analysis is to assess the efficacy of radiomics techniques utilizing magnetic resonance imaging (MRI) for predicting lymphovascular space invasion (LVSI) in patients with cervical cancer (CC).MethodsA comprehensive literature search was conducted in databases including PubMed, Embase, Cochrane Library, Medline, Scopus, CNKI, and Wanfang, with studies published up to 08/04/2024, being considered for inclusion. The meta-analysis was performed using Stata 15 and Review Manager 5.4. The quality of the included studies was evaluated using the Quality Assessment of Diagnostic Accuracy Studies 2 and Radiomics Quality Score tools. The analysis encompassed the pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), and diagnostic odds ratio (DOR). Summary ROC curves were constructed, and the AUC was calculated. Heterogeneity was investigated using meta-regression. Statistical significance was set at p ≤ 0.05.ResultsThere were 13 studies involving a total of 2,245 patients that were included in the meta-analysis. The overall sensitivity and specificity of the MRI-based model in the Training set were 83% (95% CI: 77%–87%) and 72% (95% CI: 74%–88%), respectively. The AUC, DOR, PLR, and NLR of the MRI-based model in the Training set were 0.89 (95% CI: 0.86–0.91), 22 (95% CI: 12–40), 4.6 (95% CI: 3.1–7.0), and 0.21 (95% CI: 0.16–0.29), respectively. Subgroup analysis revealed that the AUC of the model combining radiomics with clinical factors [0.90 (95% CI: 0.87–0.93)] was superior to models based on T2-weighted imaging (T2WI) sequence [0.78 (95% CI: 0.74–0.81)], contrast-enhanced T1-weighted imaging (T1WI-CE) sequence [0.85 (95% CI: 0.82–0.88)], and multiple sequences [0.86 (95% CI: 0.82–0.89)] in the Training set. The pooled sensitivity and specificity of the model integrating radiomics with clinical factors [83% (95% CI: 73%–89%) and 86% (95% CI: 73%–93%)] surpassed those of models based on the T2WI sequence [79% (95% CI: 71%–85%) and 72% (95% CI: 67%–76%)], T1WI-CE sequence [78% (95% CI: 67%–86%) and 78% (95% CI: 68%–86%)], and multiple sequences [78% (95% CI: 67%–87%) and 79% (95% CI: 70%–87%)], respectively. Funnel plot analysis indicated an absence of publication bias (p > 0.05).ConclusionMRI-based radiomics demonstrates excellent diagnostic performance in predicting LVSI in CC patients. The diagnostic performance of models combing radiomics and clinical factors is superior to that of models utilizing radiomics alone.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/#myprospero, identifier CRD42024538007.